ADVANCED ANALYSIS OF STEEL‐CONCRETE COMPOSITE BUILDINGS. Issue 1 (26th April 2023) - Tran, H.; Thai, H.T.; Ngo, T.; Uy, B.; Li, D.; Mo, J.
Abstract: This paper presents a nonlinear simulation method for composite framing systems constituted from concrete‐filled steel tubular columns (CFST) and composite beam systems. A force‐based fibre beam‐column element in OpenSees was adopted. This element was capable of accurately capturing the local buckling of steel and the confining effect of concrete using the modified stress‐strain relationships of the steel and concrete fibres. A source code for the connection element was also developed in OpenSees to capture the semi‐rigid behaviour of the beam‐to‐column connections of the composite buildings. Through the verification with numerous experiments, the model has shown its capability of accurately simulating composite frames with simplicity and less computational cost. An extensive parametric study was conducted to examine the effect of the bracing systems and the rigidity of the connections on the behaviour and instability of the whole composite buildings.